The Implementation of SST as the System of Room Reservation for Students’ Organization at Atma Jaya BSD Campus - Ferdian Aditya Pratama; Stefani Prima Dias Kristiana; Christian Moritz Lukito (SISFORMA, 2021)
The implementation of SST in any organization activity can create a positive outcome and bring less negative response if the system failed. The bureau of students, alumni, and student career counselling at Atma Jaya has difficulties managing a room booking process for the student’s organization. The current method of room booking is done manually, and it has taken a lot of costs, especially from time, human resources, and the process itself. This research focuses on developing the SST system that can help the bureau manage the room booking process. The system itself will be developed on a web-based platform using Laravel as the framework. The room booking system will be developed using an SDLC model with five general processes: planning, analysing, design, implementation, and testing. This research will also measure user satisfaction while using the system using Kaplan and Norton Model. The result of this study is a web-based system for a room booking process for students’ organizations in Atma Jaya BSD Campus. Based on the evaluation of user satisfaction, this system has an average score of 4.56, which indicates the user is very satisfied using this system for the room reservation.